L’esthétique de la lettre dans le roman et dans la peinture du XVIIIe siècle ou la représentation de la scène de lecture et d’écriture - Rabsztyn, Andrzej (Romanica Silesiana)
One cannot question the fact that a motif of a letter occupies a very significant position in the eighteenth century French paintings and literature. Although the motif of a woman reading a letter was used much earlier by the Dutch painters such as Vermeer, there are also many eighteenth century French painters (Raoux, Fragonard, Chardin or Pierre), who show women devoted to this particular activity. Thus, the popularity of letters in literature and art results from an important role correspondence played at that time. This paper emphasizes the description of a process of writing letters by a protagonist and its further influence on the receiver’s emotional and physical state of mind and body. Letters comprise a source of pleasure for both — a writer and a reader. In painting, a letter serves as the key to the interpretation of a painting, though its content is neither revealed nor comprehensible. The way of presenting characters and space, and a central position of a letter in the considered paintings may determine the interpretation — it can be treated as a signal of a relationship between lovers or its reminiscence. Considering the intimacy of the presented scene and a confidential character of a love letter, the canvas can differently predispose the receivers and make them think about sentimental intrigues. Key words: Epistolary esthetics, reading scene, writing scene, Enlightenment’s paintings, Enlightenment’s novels.